IMPLEMENTASI STEM-CP PADA PELAJARAN BIOLOGI MELALUI PEMBUATAN TEKNOLOGI FILTER EMISI UNTUK MEMBENTUK SISWA MILENIAL UNGGUL - Umi Fadilah, S.Pd. (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
In fact, biology is considered as a difficult subject because of the material offerings are too much, accompanied by latin terms, and not offering to a real object. Aspect of the learning process take the most important role in the progress of education. Thus, the teacher plays an important role in providing of of innovation values in meaningful learning. The best solution to resolve the problem is doing revitalization of the old learning strategy into a new learning strategy. The latest strategy that is intensively applied in developed countries is the STEM-based approaches (Science, Technology, Engineering, and Mathematics). The aims of STEM is build superior human resources with a wide range of competency mastery. Responding to this case, this paper provides an overview of the implementation of STEM in Biology learning in class XI MAN 2 Tuban, especially in the Respiratory System material, by using the application pattern of STEMCP based learning. In a concrete way, students can solve the problem of air emissions due to lime-mining activities in the Tuban region by utilizing Siwalan coir waste as a microfilter paper, then used as a raw material for making non-disposable masks that have the opportunity as an entrepreneurial business.